Academic librarians' perceptions of the benefits and challenges of adopting e-learning for continuing professional development in Lagos state, Nigeria. Issue 7 (8th July 2014) - Ngozi Anasi, Stella; Ali, Hussaini
Abstract : Purpose: – The aim of this paper is to examine and discuss academic librarians' perceptions of the benefits and challenges of adopting e-learning for continuing professional development. Design/methodology/approach: – To elicit the necessary information, this study adopted a descriptive survey design, using questionnaire as instrument for data collection. The study population consists of five tertiary institutions – two universities, two polytechnics and one college of education, selected as sample using the purposive sampling technique. The study also conducted a literature review on studies done on benefits and challenges of e-learning for professional development. The literature review is built on resources from online and offline. Findings: – Academic librarians in Lagos State were unanimous in their perception of benefits and challenges of adoption of e-learning for continuing professional development. The major benefits of e-learning were that e-learning opens up new frontiers for professional learning, supports knowledge generation and management and gives librarians an opportunity to broaden their knowledge. However, the major challenges to adopting e-learning for continuing professional development were inadequate power supply, inadequate knowledge of how to operate e-learning tools and limited bandwidth. Practical implications: – This paper establishes that the role of academic librarians in the provision of information for learning and study in academic institutions places them in an advantageous position to engage in e-learning activities for professional development. It also extols the need for top library management to deploy all resources within their reach to develop technology-enhanced learning system. This should also be complemented with the development and implementation of e-learning curriculum in library schools in Nigeria to inculcate e-learning culture. Originality/value: – The paper contributes to empirical research on e-learning for continuing professional development among librarians in Nigeria. Librarians who are interested in professional development will find this article useful.